Biophysical studies of metal chelate binding by HSA: Towards an understanding of metallodrug transport - Sookai, Sheldon (University of the Witwatersrand, Johannesburg, 2023)
Human serum albumin (HSA) is the most abundant blood protein, transporting many exogenous compounds including clinically deployed and investigational drugs that are generally organic in nature. HSA may largely influence the pharmacokinetics and pharmacodynamics of these drugs. Therefore, studying their interactions with HSA is vital in progressing drug development. In this thesis we present work on the synthesis and characterisation of five Schiff base bis(pyrrolide-imine) ligands that were metalated with either Au(III) (Chapters 2 and 3) or Pt(II) (Chapters 4 and 5). One of the ligands H2L1 was further metalated with Ni(II) and Pd(II) (Chapter 6). In Chapters 2 and 3 focus on a patented class of anti-cancer bis(pyrrolide-imine) Au(III) Schiff base chelates. Three Au(III) chelates were synthesized in Chapter 2 and underwent National Cancer Institute (NCI)-60 cytotoxic screening. Among them, AuL1 and AuL3 underwent full-five dose testing and recorded GI50 values of 7.3 µM and 11.5 µM, and IC50 values of 15.7 µM and 30.9 µM, respectively. AuL1 was tested further and found to be an interfacial poison of topoisomerase II at 0.5–5 µM and a catalytic inhibitor at 50 µM. In Chapter 3, two chiral tetradentate cyclohexane-1,2-diamine-bridged bis(pyrrole-imine) Au(III) complexes were reported, both of which were found to be cytotoxic in the NCI-60 screen. The chiral Au(III) chelates had a different mode of action compared to AuL1. Hierarchical cluster analysis suggest that their mode of action is similar to that of taxol. All five Au(III) chelates bound to HSA with moderate affinity (104–105 M–1) and minimally perturbed the structure of the protein. This highlights the potential for the Au(III) complexes to be transported by the HSA-mediated pathway. Chapters 4 and 5 focused on the synthesis of novel and previously reported Pt(II) Schiff base chelates to spectroscopically and computationally study their interaction with HSA and elucidate if the chelates could act as theranostic agents. It was found that switching the linking bis(imine) carbon linkage altered the binding affinity of the complex. However, the Pt(II) ion ensured that all three Pt(II) chelates preferred binding to Sudlow’s site II of HSA. The data was corroborated by molecular docking simulations and ONIOM calculations. Only 2 was found to be cytotoxic when irradiated with UV light but was found to act as a photosensitizer rather than a theranostic agent. Chapter 6 investigated the influence of d8 metal ions (Ni(II), Pd(II) and Pt(II) within the same ligand scaffold (H2PrPyrr) binding to HAS, which was investigated by steady state fluorescence quenching. The affinity constants, Ka, ranged from -3.5 -103 M−1 to-1- 106 M–1 at 37 C, following the order Pd(PrPyrr) > Pt(PrPyrr) > Ni(PrPyrr) >H2PrPyrr. The Pd(II) chelate was prone to hydrolysis and had a unique binding mode which we attribute to the unusually high binding affinity. The complexes uptake is enthalpically driven, hinging mainly on London dispersion forces. In summation, twelve metal complexes were successfully synthesized, of which 11 bound to HSA with a moderate binding affinity. The Au(III) chelates preferred Sudlow’s site I, while the Pt(II) chelates preferred Sudlow’s site II. Overall, the metal complexes bound fully intact to HSA.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Human serum albumin; Ligand; Metallodrug; Schiff base chelate; Gold; Platinum; Cancer; Stern-Volmer; UCTD; SDG-3: Good health and well-being